PERSONAL: Feasibility Study Protocol for Placebo-Controlled, Randomized n-of-1 Trials of Tamsulosin for Lower Urinary Tract Symptoms - Bauer, Scott R.; Breyer, Benjamin N.; Oni-Orisan, Akinyemi; Steinman, Michael A.; Sim, Ida; McCulloch, Charles E.; Kenfield, Stacey A. (Frontiers in Digital Health, 2020)
Lower urinary tract symptoms (LUTS) affect more than half of men over age 70 and contribute to poor health-related quality of life and polypharmacy. Tamsulosin hydrochloride is the most common medication used to treat LUTS due to benign prostatic hyperplasia and is often prescribed indefinitely, although not all men benefit from long-term therapy. N-of-1 trials allow for individualized estimates of benefit and harm and could facilitate decisions regarding chronic tamsulosin therapy for LUTS, particularly among older men. Our team developed the PERSONAL (PlacEbo-controlled, Randomized, patient-Selected Outcomes, N-of-1 triALs) app to track daily urinary symptoms and medication side effects for n-of-1 trials among older men. We will conduct a feasibility study of 20 individual randomized n-of-1 trials using the PERSONAL app to compare tamsulosin versus placebo. Participants will work with research staff to prospectively identify the most important urinary symptoms and medication side effects that they would like to digitally track. Our primary outcomes for this study will be recruitment and retention of eligible men, completion rates of n-of-1 trials and daily questionnaires using the PERSONAL app, and participants’ perceived usefulness of their n-of-1 trial for determining whether tamsulosin is effective for them. Linear mixed effects models with individual-specific intercepts and intervention effects will also be used to estimate within-individual effects of tamsulosin. The goal of this innovative study is to establish feasibility and acceptability of using a mobile health app and n-of-1 trials to provide older men with individualized estimates of benefits and harms of chronic tamsulosin therapy for LUTS.